Frequency of secondary tonsillectomy in Germany - Schieferbein, V; Windfuhr, J P (HNO, 2021)
Tonsillar remnants are occasionally the subject of clinical negligence claims in tonsillectomy patients, but obligatory in every tonsillotomy procedure. In both cases, clinically relevant symptoms can require a secondary tonsillectomy (STE). The purpose of this retrospective longitudinal study was to identify the prevalence of STE in Germany between 2005 and 2018, using a report commissioned by the Federal Office for Statistics. STE was identified using the operation and procedure key (Operationen- und Prozedurenschlüssel, OPS) code 5‑281.4, and the prevalence stratified by year, age, and gender. Linear regression analysis was performed. In addition, the prevalence of tonsillectomy and tonsillotomy was determined by the OPS codes 5‑281.5, 5‑281.0, and 5.282.0. Between 2005 and 2018, 11,018 patients underwent STE in Germany. The total number of STE per year decreased significantly from 1080 in 2005 to 483 in 2018 (p < 0.001). The number of inpatient tonsillotomy cases increased between 2007 and 2018 from 4658 to 18,369. The annual number of STE in Germany decreased continually during the observation period. The population-based data used in the study were insufficient to determine whether STE had been performed after tonsillectomy or tonsillotomy. Further patient-level research is thus required.